Inframammary Fold Reconstruction: A Biomechanical Analysis. Issue 3 (March 2016) - Eichler, Christian; Schell, Julia; Uener, Jens; Prescher, Andreas; Scaal, Martin; Puppe, Julian; Warm, Mathias
Abstract : Background: Inframammary fold reconstruction has scarcely been evaluated in literature. No biomechanical analyses have been performed comparing different reconstructive methods. This evaluation compares the gold-standard suture reconstruction with an intrarib anchor system (Micro BioComposite SutureTak, Arthrex). Methods: Three analysis groups were compared including 8 Sawbone blocks, 22 embalmed cadaver, and 27 regular cadaver specimens (N = 57). Transient mechanical analysis was performed at 5 N/s using an Instron 5565 test frame. Results: Ultimate load favored the anchor system (compared with the gold-standard suture) by a factor of 9.8 ( P < 0.0001) for the regular cadaver group and a factor of 1.7 ( P < 0.038) for the embalmed cadaver group. A similar statistically significant benefit was shown for stiffness and load at 2-mm displacement. Conclusions: This analysis showed an anchor system to be the biomechanically superior fixation method in terms of ultimate load, fixation stiffness, and displacement at failure when compared with the gold-standard suture method in inframammary fold reconstruction. Because of superior stability in every aspect, an anchor system may be considered for inframammary fold reconstruction.